2020
DOI: 10.1111/evj.13268
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synergy of eugenol on the antifungal effects of voriconazole against Candida tropicalis and Candida krusei strains isolated from the genital tract of mares

Abstract: Background: Due to the limited range of antifungals available to treat genital Candida infections and the emergence of resistant isolates, attention has focused on the antifungal potency of natural compounds with promising biological properties. Objectives: To examine whether eugenol synergises the in vitro efficacy of voriconazole against Candida strains isolated from the genital tract of mares. Study design: In vitro experiment. Methods: The antifungal activity of eugenol and voriconazole was evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our research also shows that the constituent of Eugenia caryophyllata essential oil – eugenol – enhances miconazole and econazole action. The latest research of Sharifzadeh and Shokri [30] confirm the ability of eugenol to synergistic action with antimycotic agents against yeast form Candida genus. The authors showed that eugenol in combination with voriconazole possess synergistic potential against C. tropicalis and C. krusei isolates (FICI=0.19–0.88).…”
Section: Discussionmentioning
confidence: 91%
“…Our research also shows that the constituent of Eugenia caryophyllata essential oil – eugenol – enhances miconazole and econazole action. The latest research of Sharifzadeh and Shokri [30] confirm the ability of eugenol to synergistic action with antimycotic agents against yeast form Candida genus. The authors showed that eugenol in combination with voriconazole possess synergistic potential against C. tropicalis and C. krusei isolates (FICI=0.19–0.88).…”
Section: Discussionmentioning
confidence: 91%
“…Eugenol, being a phytochemical, has already been reported to have antifungal activity in Candida spp. The MIC of eugenol have been reported in the range of 375–750 µg/mL against Candida dubliniensis and Candida tropicalis and 200–400 µg/mL against Candida krusei ( De Paula et al., 2014 ; Sharifzadeh and Shokri, 2021 ). Eugenol containing essential oils were found to transform the hyphal ultrasound and virulence factors of A. fumigatus and Trichophyton rubrum ( Gayoso et al., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a synergistic effect of eugenol in combination with voriconazole against voriconazole-resistant C. tropicalis and C. krusei isolated from the genital tract of mares ( Sharifzadeh and Shokri, 2021 ). To this end, Dąbrowska et al (2021) reported that eugenol indicated additive and synergistic activities with econazole and miconazole against clinical isolates of C. albicans , respectively.…”
Section: Combination Therapymentioning
confidence: 99%